2014
DOI: 10.1080/1461670x.2014.906930
|View full text |Cite
|
Sign up to set email alerts
|

Exploring New Frontiers of Agenda Building During the 2012 US Presidential Election Pre-Convention Period

Abstract: Grounded in an agenda-building theoretical perspective, this study explored in depth the relationships between political campaign information subsidies and elite national news media coverage. Specifically, this investigation examined three levels of agenda-building linkages (object, attribute, and network connections) simultaneously during the 2012 US Presidential Election pre-convention period between Barack Obama (Democrat) and Mitt Romney (Republican). A total of 2655 campaign information subsidies and 345 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Empirical evidence is quite strong that influences through information subsidies on journalistic news selection and media coverage exist. Particularly during election times, it was demonstrated that public relations efforts by political candidates-also in the online sphere-influence media coverage (Kiousis et al 2015;Kiousis et al 2006;Lancendorfer and Lee 2010). Similar results can be found for routine, nonelection communication by political institutions, such as the U.S. Congress (Kiousis et al 2011).…”
Section: Theoretical Background: Agenda-building and Twittermentioning
confidence: 70%
See 1 more Smart Citation
“…Empirical evidence is quite strong that influences through information subsidies on journalistic news selection and media coverage exist. Particularly during election times, it was demonstrated that public relations efforts by political candidates-also in the online sphere-influence media coverage (Kiousis et al 2015;Kiousis et al 2006;Lancendorfer and Lee 2010). Similar results can be found for routine, nonelection communication by political institutions, such as the U.S. Congress (Kiousis et al 2011).…”
Section: Theoretical Background: Agenda-building and Twittermentioning
confidence: 70%
“…The information subsidy approach mainly considers one direction of influence in the agenda-building process-influence from the political system on journalists and media coverage. Political communication researchers followed this approach by analyzing the influence of political public relations on media coverage (Berkowitz 1987;Kiousis et al 2015;Kiousis et al 2006;Turk 1986), investigating the influence of press releases by politicians or political parties on journalists' information selection and news media coverage (Lancendorfer and Lee 2010;Turk 1986). That there is an influence of political information on journalism is natural since journalists need political sources for their coverage.…”
Section: Theoretical Background: Agenda-building and Twittermentioning
confidence: 99%
“…One example is Entman's slightly revised definition of framing as “selecting and highlighting some facets of events or issues, and making connections among them so as to promote a particular interpretation, evaluation, and/or solution” (Entman, , p. 417). Associations with attributes, actors, and other issues and connections between them can also be conceived as semantic networks (Baden, ; Guo, ; Hellsten, Dawson, & Leydesdorff, ; Kiousis et al, ; Schultz, Kleinnijenhuis, Oegema, Utz, & van Atteveldt, ), in which the meaning of separate concepts derives from their multiple relationships and the latter's integration (Schultz et al, ). Their co‐occurrence in news items creates asymmetric associations (Ruigrok & van Atteveldt, ; Tversky, ) in which specific concepts (e.g., doves, derivatives) are more strongly associated with more general concepts (e.g., birds, banks) than the other way around.…”
Section: Observing Communicative Complexity On the Level Of Agendas Amentioning
confidence: 99%
“…Agenda setting analyzes the transfer of object salience from the media to the public (McCombs & Shaw, , first‐level agenda setting). Research on higher‐level agenda setting (Carroll & McCombs, ; Guo, ; Kiousis et al, ; McCombs & Reynolds, ) and framing (Entman, ; D. A. Scheufele & Tewksbury, ) maintains that the general public will assign attributes and associations to first‐level objects, such as issues and actors, that are predominant in the media of their choice. Communicative complexity serves as an overarching label to refer to the variety or diversity of objects on the media agenda and of the connections between them in media frames.…”
mentioning
confidence: 99%
“…Obama supporters tended to follow the network agenda of vertical mainstream media, whereas Romney supporters were more in line with the conservative niche media. Kiousis et al (2014) used the model to evaluate and measure public relations effects. From an agenda-building theoretical perspective, the researchers examined the impact of political campaign information subsidies (e.g., news releases, campaign blogs) on national media coverage during the 2012 U.S. presidential election preconvention period.…”
Section: Theoretical Framework the Network Agenda Setting Modelmentioning
confidence: 99%